Recommendations for the assessment and management of measurable residual disease in adults with acute lymphoblastic leukemia: A consensus of North American experts. Issue 2 (26th November 2018) - Short, Nicholas J.; Jabbour, Elias; Albitar, Maher; de Lima, Marcos; Gore, Lia; Jorgensen, Jeffrey; Logan, Aaron C.; Park, Jae; Ravandi, Farhad; Shah, Bijal; Radich, Jerald; Kantarjian, Hagop
Abstract: Measurable residual disease (MRD) that persists after initial therapy is a powerful predictor of relapse and survival in acute lymphoblastic leukemia (ALL). However, the optimal use of this information to influence therapeutic decisions is controversial. Herein, we comprehensively review the role of MRD assessment in adults with ALL, including methods to quantify residual leukemia cells during remission, prognostic impact of MRD across ALL subtypes, and available therapeutic approaches to eradicate MRD. This review presents consensus statements and provides an evidence‐based framework for practicing hematologists and oncologists to use MRD information to make rational treatment decisions in adult patients with ALL.